Organoleptic and Chemical Properties of SERANGI Herbal Drink: A Blend of Lemongrass (Cymbopogon nardus L.) and Holy Basil (Ocimum sanctum L.) as Immune Booster. - Ambar Fidyasari; Ayu Ristamaya Yusuf; Nafila Nada Dzikri (Universitas Muhammadiyah Malang, 2024)
Herbal drinks have therapeutic and refreshing properties. Some plethora of botanicals are used as herbal drink ingredients, including simplicia from lemongrass (Cymbopogon nardus L.) and holy basil (Ocinum sanctum L.). This research was performed to assess the organoleptic and chemical characteristics of lemongrass and holy basil simplicia herbal drink named Serangi. The research underwent two phases: organoleptic testing in the first stage and chemical analysis in the second stage to evaluate pH, vitamin C levels, and total phenols in Serangi herbal drink. Three repetitions had been performed to gain data mean values and standard deviation before being analyzed using General Linear ANOVA model (GLM) on the Minitab 20 software. Results revealed panelists' preferences for F3 in terms of color, aroma, and taste, with ratings of 4.12, 4.02, and 4.05, respectively. All Serangi drink samples met the pH requirements, falling within the 3-8 range, where F3 exhibited the highest vitamin C content of 1.224% and total phenol content of 122.10 mg GAE/100g/ml. Serangi herbal drink is rich in vitamin C and secondary metabolites and it offers immune-boosting benefits.